The Fate of Factor VII and Stuart Factor During the Clotting of Normal Blood - Johnston, Charles L, jr.; Ferguson, John H; O’Hanlon, Frieda A; Black, W. L (Thrombosis and Haemostasis, 1959)
Studies have been presented, utilizing factor specific assays, to show that Factor VII and Stuart factor behave differently during the clotting of normal blood. Stuart factor was neither consumed nor activated during clotting. In contrast, Factor VII was “activated” so that serum contained 2V2 to 3 times the plasma concentration of the factor. Marked rate changes occurred in the Factor VII activation curves when the sample incubation temperature was changed. The data obtained suggested that the optimum temperature for Factor VII activation may be at or near 18° C. Previous “consumption” data for “Factor VII” obtained by assays sensitive to changes in both Stuart factor and Factor VII have been validated, since the concentration of Stuart factor does not change during clotting.